Laser texturing of glass for modified surface energy and hydrophobicity - Abdul Fattah, Mohamad Tahir; Syarifah Nur Aqida, Syed Ahmad; Izwan, Ismail; Nur Ezrin, Mad Sarif (Malaysian Tribology Society (MYTRIBOS), 2025)
The use of hazardous chemicals as a secondary process in glass surface modification contradicts the aspirations of Sustainable Development Goals. Opting for laser surface texturing, hydrophilic soda lime silica glass surface can be transformed into a hydrophobic state by manipulating its surface energy. To date, findings on the effect of roughness profile on surface energy are still limited. This study investigated a facile methodology for examining wettability, surface energy and surface topography resulting from variations in laser fluence, hatch pattern and spacing. The assessment of wettability according to ASTM D7490 and ASTM D7334 was conducted using distilled water, while surface topography was evaluated based on the ISO4287 standard. The sessile drop test reveals that samples with a spacing interval of 0.06 mm recorded a maximum water contact angle of 96° which equivalent to 26.98 mJ/m2; resulted in complete transformation into a hydrophobic state. Samples with Rz value greater than 23 μm generally exhibited lower wettability surface compared to pristine glass and promoted lower surface energy. These findings are significant for tailoring the roughness profile of glass using laser processing technique, which has the potential to modify the wettability of glass.